An econometric approach for evaluating the cost efficiency in post reform era: empirical evidence from the Indian electricity supply industry. (2016) - Khetrapal, Pavan; Thakur, Tripta
In Indian electricity supply industry, the state electricity regulatory commissions presently follow rate-of-return regulation for setting the retail tariff for distribution utilities. However, the current approach of tariff determination does not guarantee any incentives to the utilities to reduce their operating costs and often leads to arbitrary decision making. Accordingly, a performance-based regulatory mechanism has been recognised as an alternative approach to the traditional rate-of-return regulation and most of the state electricity regulatory authorities are now in the process of implementing performance-based regulation regime for setting the distribution tariff. This paper analyses the cost efficiency of 58 Indian electricity distribution utilities during the period 2008/09-2011/12. The estimated 'best' practice frontier could be used by Indian state electricity regulatory authorities as a benchmark to control utility's cost and further could be served to provide preliminary base for implementing performance based regulation in Indian electricity supply industry.